Social Protection in Health : What Are the Options for Pakistan? - World Bank (Washington, DC, 2017)
The main objective of this note is to outline the issues that need to be considered at the planning stage; and to analyze what are the options for Government of Pakistan (GOP) to consider extending social protection to health. Because the potential beneficiaries also access publicly?financed services from the public health sector, and because they are a large share of the supposed target beneficiaries of parallel initiatives financed by the Government, the Bank recommends that a team, including members from Benazir Income Support Program (BISP), Ministry of Finance, Federal Ministry of health and the provincial governments be formed to discuss pros and cons of alternative design features. The Bank will be pleased to support this effort. This is the first of the policy note series on social protection in health by South Asia Human Development Sector (SASHD). Policy note dilates the essential principles and critical issues in the design of a social health insurance model and also presents various options available to extend health insurance to the target population (poor and vulnerable).